Incorporating intellectual playfulness in writing instruction for high ability ESL students in Malaysian secondary schools / Hemadevi Chandaran - Hemadevi , Chandaran (2019)

(untitled)
The purpose of this research was to explore intellectual playfulness a construct adapted from Fine (2014) which marries open-ended tasks with opportunities for risk- taking and complete engagement. The study has implemented playfulness and ambitious instruction into teaching of writing of high ability students. It is an effort to conceptualize an alternate reality for high ability students to move towards learning dispositions and have cognitive rigor and pleasurable engagement in ESL writing classroom. The study was conducted using qualitative research approach where analysis done using interviews, classroom interactions, students’ and researcher’s journal entries and students’ compositions. The findings has indicated the phrase ‘What if…’ that used as instructions in the writing tasks has promoted learning and self-discovery among high ability students in the writing classroom. In searching the changes of intellectual playfulness from three qualities that is stated in Fine’s Theory of Intellectual Playfulness, the findings has revealed open-endedness gave students freedom and flexibility to move and engage in higher order skills as well as the empowerment to explore their thoughts without restrictions. The findings further specified students were moving from the continuum of being risk-adverse to being risk-takers and redesigning their knowledge i.e writing beyond examination needs in the writing tasks. They were also attentive and focused in the writing lessons and seem to lose track of time since they completely absorbed or engaged in the task. The three qualities of intellectual playfulness explored in this study has provided a promising platform for high ability adolescents in conceptualizing a pedagogy that links cognitive rigor and engagement in writing as suggested by Fine (2014). The findings has highlighted intellectual playfulness extended students horizon beyond the text book knowledge to real-world experiences and promoting creativity in their writing. The study also presented contributions to individual qualities through high cognitive flexibility, high learning goal orientations and high cognitive engagement which constitute a new learning disposition in the context of writing in school that enables students to discuss more effectively the affordances of engaging with intellectual playfulness. It is hoped that the findings of this research rejuvenates high schools to boost rigor of traditional academic of knowledge and provides opportunities for high ability students to navigate writing with rigor and pleasure in ESL writing classroom.